LRBA deficiency: a rare cause of type 1 diabetes, colitis, and severe immunodeficiency - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2021)
The biological role of the lipopolysaccharide-responsive beige-like anchor (LRBA) protein associated with the immune system is not to date well known. However, it is thought to regulate the CTLA4 protein, an inhibitory immunoreceptor. Chronic diarrhea, autoimmune disorders, organomegaly, frequent recurrent infections, hypogammaglobulinemia, chronic lung manifestations, and growth retardation are some features of LRBA deficiency. This rare disease is observed as a result of homozygous mutations in the LRBA gene. An 11.3-year-old male patient presented because of short stature and high blood glucose level. He had a previous history of lymphoproliferative disease, chronic diarrhea, and recurrent infections. His parents were first-degree consanguineous relatives. A diagnosis of type 1 diabetes mellitus (T1DM) was added to the preexisting diagnoses of immunodeficiency, recurrent infection, enteropathy, chronic diarrhea, lymphadenopathy, hepatomegaly, and short stature. Genetic analysis revealed a homozygous mutation in the LRBA gene, c.5047C>T (p.R1683*) (p.Arg1683*). Abatacept treatment was started: the patient's hospital admission frequency decreased, and glucose regulation improved. At follow-up, growth hormone (GH) deficiency was diagnosed, although it was not treated because the underlying disease was not under control. Nevertheless, the patient's height improved with abatacept treatment. LRBA deficiency should be considered in the presence of consanguineous marriage, diabetes, immunodeficiency, and additional autoimmune symptoms. LRBA phenotypes are variable even when the same variants in the LRBA gene are present. Genetic diagnosis is important to determine optimal treatment options. In addition to chronic malnutrition and immunosuppressive therapy, GH deficiency may be one of the causes of short stature in these patients.
Keywords: Autoimmunity; Enteropathy; LRBA; Short stature; Type 1 diabetes mellitus; IMMUNE DYSREGULATION; MUTATIONS; AUTOIMMUNITY